KOMPOSITION UND PERSONENFÜHRUNG IN XENOPHONS SYMPOSION ALS PARADIGMA SEINER ERZÄHLKUNST. - Kaiser, Otto (TRAMES: A Journal of the Humanities & Social Sciences, 2015)
Xenophon's Symposium is a carefully composed book that captivates his readers from the first to the last line. It offers a view of the extensive conversation through-out the dialogue. Participants explain in conversation what they are most proud of and how they must think about the meaning of life and about their own destiny.